Synthesis And Characterization Of Ester Trimethylolpropane Based Jatropha Curcas Oil As Biolubricant Base Stocks - Arbain, Noor Hafizah; Salimon, Jumat (Journal of Science and Technology, 2010)
Biolubricant production of ester trimethylolpropane (ET) was conducted via esterification of fatty acid (FA) of Jatropha curcas oil with trimethylolpropane (TMP). The condition for this reaction was as follows: temperature was 150°C, time of reaction was 3 hours, molar ratio of FA: TMP was 4:1, and 2 % w/w catalyst (based on weight of FA). Sulfuric acid was used as the catalyst in this reaction. The composition of ET was determined by gas chromatography (GC-FID). The ester group was confirmed by fourier transform infrared spectroscopy (FTIR) and the structure was confirmed by proton and carbon Nuclear Magnetic Resonance (1H-NMR and 13C-NMR) spectra. 55% of product was successfully synthesized in this research. The pour point of the product was observed as low as –30°C, flash point was >300 °C and viscosity was 79 cP.